(untitled) (International journal of artificial intelligence, 2025)
This article discusses the theoretical and practical aspects of developing the historical thinking of future teachers through the use of elements of theater pedagogy. The importance of theatrical lessons, dramatic play, role-playing and interactive staging as innovative methods in history is analyzed. The study reveals the influence of personal participation, emotional experience and creative expression on the acquisition of historical knowledge.